2016
DOI: 10.1186/s12890-016-0234-0
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of initiating extrafine-particle versus fine-particle inhaled corticosteroids as asthma therapy in the Netherlands

Abstract: BackgroundMost randomised clinical trials typically exclude a significant proportion of asthma patients, including those at higher risk of adverse events, with comorbidities, obesity, poor inhaler technique and adherence, or smokers. However, these patients might differentially benefit from extrafine-particle inhaled corticosteroids (ICS). This matched cohort, database study, compared the effectiveness of extrafine-particle with fine-particle ICS in a real-life population initiating ICS therapy in the Netherla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
15
1
1
Order By: Relevance
“…LCI was associated with S cond only, suggesting that abnormalities in the conducting rather than the acinar airways determined the higher LCI in the patients with asthma. Neither S acin nor S cond showed significant reversibility post-bronchodilation in this study [49].…”
Section: The Role Of Washout Tests In Asthmacontrasting
confidence: 70%
See 1 more Smart Citation
“…LCI was associated with S cond only, suggesting that abnormalities in the conducting rather than the acinar airways determined the higher LCI in the patients with asthma. Neither S acin nor S cond showed significant reversibility post-bronchodilation in this study [49].…”
Section: The Role Of Washout Tests In Asthmacontrasting
confidence: 70%
“…Detection of distal airway pathology, in particular, may be important because peripheral airways are less accessible to inhaled medication, and a different therapeutic approach, including extra-fine particle ICSs or systemic steroid treatment, may be required to treat pathology that is predominantly situated in the peripheral airways. A population study involving a large cohort of adult asthmatics found that patients prescribed an extra-fine particle ICS (<2 µm particle size) were less likely to experience asthma attacks, had better overall asthma control and required a lower prescribed ICS dose to achieve this compared with patients prescribed standard-particle ICSs [49]. We hypothesise that this benefit is due to improved distribution of the inhaled medication into the small airways.…”
Section: The Role Of Washout Tests In Asthmamentioning
confidence: 88%
“…Одно из наиболее детальных исследований эффективности терапии мелкодисперсными аэрозолями ИГКС в условиях реальной клинической практики было проведено van der Molen et al [40]. Исследуемая популяция, выбранная в базе данных Нидерландов (Pharmo Database Network), включала пациентов в возрасте от 12 до 60 лет с диагнозом «бронхиальная астма», установленным врачами общей практики.…”
Section: влияние циклесонида на мдп у больных баunclassified
“…The original version of this article [ 1 ] unfortunately contained errors that have since been corrected.…”
Section: Erratummentioning
confidence: 99%